2022
DOI: 10.3389/fcell.2022.829435
|View full text |Cite
|
Sign up to set email alerts
|

miR-30d-5p: A Non-Coding RNA With Potential Diagnostic, Prognostic and Therapeutic Applications

Abstract: Cancer is a great challenge facing global public health. Scholars have made plentiful efforts in the research of cancer therapy, but the results are still not satisfactory. In relevant literature, the role of miRNA in cancer has been widely concerned. MicroRNAs (miRNAs) are a non-coding, endogenous, single-stranded RNAs that regulate a variety of biological functions. The abnormal level of miR-30d-5p, a type of miRNAs, has been associated with various human tumor types, including lung cancer, colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 112 publications
0
3
0
1
Order By: Relevance
“…MiR-766-3p was reported to act as a tumor suppressor in different types of cancers [ 43 , 44 ], but, to the best of our knowledge, its role in glioma has not been investigated. On the other hand, miR-30d-5p was demonstrated to be involved in the development and progression of different types of cancers [ 45 ], but, to the best of our knowledge, its involvement in glioma progression has not been investigated. It has been reported that miR-625-5p inhibits glioma cells’ proliferation, migration and invasion and increases their chemosensitivity [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-766-3p was reported to act as a tumor suppressor in different types of cancers [ 43 , 44 ], but, to the best of our knowledge, its role in glioma has not been investigated. On the other hand, miR-30d-5p was demonstrated to be involved in the development and progression of different types of cancers [ 45 ], but, to the best of our knowledge, its involvement in glioma progression has not been investigated. It has been reported that miR-625-5p inhibits glioma cells’ proliferation, migration and invasion and increases their chemosensitivity [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been proposed that the GBP1P1 expression profile could predict a complete response to chemotherapy in early BC 50 . The hsa-miR-30d-5p dysregulation has been reported in several cancers 63 . The hsa-miR-30d-5p downregulation has been reported in single hormone receptor-positive breast cancer 64 .…”
Section: Discussionmentioning
confidence: 99%
“…There is little literature evidence to link the studied miRNAs to SB. Some of them have been connected to neoplastic disease development (miR-1253, miR-1290, miR-194-5p, miR-4536-5p, miR-548ar-5p, miR-590-5p, miR-627-5p, miR-320e, miR-23a-3p, miR-612, miR-23a-3p, miR-30d-5p, and miR-122-5p) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The role of let-7b-5p in neuronal development and neuroinflammation has been demonstrated [ 25 ].…”
Section: Discussionmentioning
confidence: 99%